Analisis Minat Masyarakat Menjadi Nasabah Dana Pihak Ketiga Bank Syari’ah di Kota Tasikmalaya - Asep Suryanto (IQTISHODUNA: Jurnal Ekonomi Islam, 2017)
The purpose of this study was to identify the community interest to become customers in Islamic banks in the city of Tasikmalaya. The method used is descriptive method with qualitative approach. The technique of data analysis is conducted qualitatively by an interactive model, with the following steps: describing, classifying or categorizing, data analysis, and conclution or drawing. The results showed that the interest of the community to become customers of depositors’ funds of Islamic banks is characterized by high attractiveness of the elements of reason interest is product services Shariah compliance, halal rewards, strategic location, the promotion of which is integrated with the values of Islam, the service process and standards emphasizes hospitality, the image of islamic banks reflected with investments heavily secured, morality and professionalism of employees, the physical evidence that supports ease of service, the importance of transparency in the nisbah / margin and financial reports, Islamic banks functioning civil society in collecting and distributionof zakat, infaq, and charity.